2019
DOI: 10.1016/j.shpsb.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Timelike entanglement for delayed-choice entanglement swapping

Abstract: Experiments involving delayed-choice entanglement swapping seem to suggest that particles can become entangled after they've already been detected. This astonishing result is taken by some to undermine realism about entanglement. In this paper, I argue that one can offer a fully realist explanation of delayed-choice entanglement swapping by countenancing timelike entanglement relations. I argue that such an explanation-radical though it may be-isn't incoherent and doesn't invite paradox. I compare this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…32 Relatedly, earlier work suggested the development of the idea of temporal entanglement in standard quantum mechanics, but the task encountered technical difficulties. See (Glick 2019, Adlam 2018) for a review. can be encountered in the context of quantum nonseparability of quantum states can be extended to the (formal) indefiniteness of spatiotemporal relations encountered in the context of causal nonseparability of process matrices.…”
Section: Back To Standard Quantum Mechanicsmentioning
confidence: 99%
“…32 Relatedly, earlier work suggested the development of the idea of temporal entanglement in standard quantum mechanics, but the task encountered technical difficulties. See (Glick 2019, Adlam 2018) for a review. can be encountered in the context of quantum nonseparability of quantum states can be extended to the (formal) indefiniteness of spatiotemporal relations encountered in the context of causal nonseparability of process matrices.…”
Section: Back To Standard Quantum Mechanicsmentioning
confidence: 99%
“…We introduce entanglement swapping by following a helpful recent presentation by Glick [15]. As Glick puts it: Entanglement swapping is a procedure in which entanglement may be "swapped" from a pair of jointly measured particles to a pair of particles lacking common preparation.…”
Section: Entanglement Swappingmentioning
confidence: 99%
“…Think of the sensitivity of the causal structure of a regular ∨-shaped EPR-Bell experiment to the time-order of measurements, in any collapse model. In our view, it is worth asking whether there are models that avoid this consequence, especially given that the experimental correlations are independent of the temporal location of C. 15…”
Section: Summary: CL In the Actual Delft Experimentsmentioning
confidence: 99%
“…Finally, Schaffer (2010) has argued that entanglement cannot be a single relation since both two, three and N particles can be entangled. Neither will be dealt with here, and the reader is referred to Timpson and Brown (2010) for a reply to Seevinck, Egg (2013) and Glick (2019) for a reply to Healey, and in reply to Schaffer, it will be observed that entanglement can always be regarded as a relation between a subsystem and the rest of the system (see Sect. 3 for further details and Morganti (2009) for further discussion).…”
Section: Introductionmentioning
confidence: 99%